Agama dan Kesadaran Menjaga Lingkungan Hidup - Safrilsyah Safrilsyah; Fitriani Fitriani (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Religion and environment are seen as separated and unrelated discourses. This understanding positions religion to unlikely give any contribution in enhancing Muslims awareness on environment. Actually, in Islamic concept, the Quran frequently mentions environment in different ways as a basic conception on environment. At least there are three concepts introduced by the Quran; al-bi’ah, al- mubahat, marafiq al-balad. Al-bi’ah (occupying a territory, life space and environment) perceives environment as a living space especially for humankind. Through the concept of Muhabat, Islam treats forest ecosystem as a free space. There are two categories in this concept. Firstly, environment is seen as a death earth (al- mawat) if the forests are wild jungles and remote from human territories. When the forests are geographically around human territories, so they fall under the second category that is marafiq al-balad (edge earth). This article explores the Islamic concept on environment which is introduced by contemporary Muslim scholar, Yusuf al-Qardhawi. According to him, there are some concepts in Islam that are related to protecting environment. These concepts are of al-istishlah (shared benefit), maqashid al-syari’ah, and Sunnah. This article is also enriched by Fitri’s thesis that explores the role of religion and the awareness to protect environment in Simpang Tiga sub-disctict, Pidie of Aceh province. Her research finds that some of community religious activities are not correlative with the awareness in protecting environment.